PERBAIKAN TATA LETAK FASILITAS DENGAN MENGGUNAKAN METODE SYSTEMATIC LAYOUT PLANNING (SLP) PADA PT. X - Wahyu Nurul Hidayat, (2021)
PT. X is an enterprise service management of waste bins which have an area to manage waste bins called House Restoration Materials (RPM). Companies face the problem that the flow process that occurs with the layout when it often happens complaints from operators because of relationship closeness between that area has not been mutually related, The company also wants to expand the area of reception and storage bins so that the capacity increases, as well as minimize happens to confuse the bags of garbage between clients. By because it is, necessary repair procedures lies in the area of RPM PT. X are structured by using the method of Systematic Layout Planning (SLP). SLP is used for planning of alternative governance lies with relationship closeness and the flow of material at a distance shortest, from research it obtained the total needs of wide-area RPM at 1287.821 m² with 21 area that needed therein. Research is generating two alternatives proposed layout, namely the proposed layout first to produce a total distance of movement of the material amounted to 603.75 m², while for the proposed layout second produces a total distance of movement of the material at 602,5 m². Result elect of second proposals that area proposed alternative layout both due to having several advantages, namely a distance of transfer of the material is short and the proposals it provides space empty to be used as a road or area storage addition. Of the proposed alternative layout second resulting savings within the transfer material so large 15.20% of the layout existing.